Mental health and social difficulties of late‐diagnosed autistic children, across childhood and adolescence. (16th February 2022) - Mandy, Will; Midouhas, Emily; Hosozawa, Mariko; Cable, Noriko; Sacker, Amanda; Flouri, Eirini
Abstract : Background: Autism can be diagnosed from 2 years of age, although most autistic people receive their diagnosis later than this after they have started education. Research is required to understand why some autistic children are diagnosed late, and the level and nature of unmet need prior to diagnosis for late‐diagnosed children. Methods: We examined trajectories of emotional, behavioural and social difficulties (EBSDs) across childhood and adolescence, comparing 'earlier‐diagnosed' (diagnosed 7 years or younger) with 'late‐diagnosed' (diagnosed between 8 and 14 years) autistic children. Data were from the Millennium Cohort Study, a population‐based UK birth cohort. EBSDs were measured using the parent‐report Strengths and Difficulties Questionnaire, at 3, 5, 7, 11 and 14 years. We used Growth Curve Modelling to investigate levels and rates of change in these difficulties, and to compare earlier‐ ( n  = 146) and late‐diagnosed ( n  = 284) autistic children. Results: Aged 5, earlier‐diagnosed autistic children had more emotional (i.e., internalising), conduct, hyperactivity and social difficulties; although clinical difficulties in these areas were nevertheless common in late‐diagnosed children. There was a faster annual increase in scores for all domains for late‐diagnosed children, and by age 14 years, they had higher levels of EBSDs. These results persisted when we ran adjusted models, to account for the late‐diagnosed group having higher rates of late‐diagnosed attention deficit/hyperactivity disorder, higher IQ, a higher proportion of females and older and more educated mothers. Conclusions: Emotional, behavioural and social difficulties are associated with, and may influence, the timing of autism diagnosis. Late‐diagnosed autistic children often have high levels of mental health and social difficulties prior to their autism diagnosis, and tend to develop even more severe problems as they enter adolescence.